RUDAT DANCE SHOW PROMOTES MANDALIKA ON MOTO GP - Muhammad Sultan Hali; Khairil Anwar (Bajang Institute, 2022)
Rudat dance used to perform in traditional Sasak culture called Begawe, roah-thankful ceremonial culture based on primitif way. This nowadays left by millenial and Zillenial. Then pursued to state the problem that how to utilization of the Rudat Dance for the Mandalika Moto GP Event. This research find that Rudat can be perform to be useful Dance for this International event. This research finding indicated two types of Rudat can be used to be shown in tourism persfective. Therefore Rudat can be developed to be one of the target traditional culture to utilized by all stakeholders those who envolved to promote rudat as one of attractive for tourism event.